Legal Aspects of Ecosystem Services Related to Efficient Forest Exploitation - OLEGOVNA APSALYAMOVA, Saida; OLEGOVNA KHACHIR, Bella; ZAKIREEVICH KHUAZHEV, Oleg; KAZBEKOVICH BGANE, Yuri; KAZBEKOVNA KUFANOVA, Saida (Journal of Environmental Management and Tourism, 2016)
The legislation also provides the creation of mechanisms for keeping ecosystem values that are not covered by PES (payment for ecosystem services) schemes, for example, in case of protected areas where special laws are in force. They regulate issues related to compensation due to the introduction of limitations in relation to business activity in protected natural areas and small conservations. In case of protected areas, various taxation tools are applied, including relief from land tax in the areas, and decrease in land income tax in order to cover expenses for keeping and recovering protected forest regions. The forest ownership legal regime determines the conditions under which the PES schemes would be effectively functional, therefore it is necessary to define clearly and recognize forest tenure and exploitation modes. The mode of forest ownership is a generic notion that means various systems that grant the rights to those who own land and often determine specific terms and conditions for them.
Keywords: biodiversity; ecosystem; ecologic; scoop; forest policy; forest-related services; “green” economy; habitat; migration of loading; monitoring; payment for ecosystem services; PES; private; protection functions; society; recreation; subsidies